2014
DOI: 10.1186/2041-9139-5-38
|View full text |Cite
|
Sign up to set email alerts
|

Toll signals regulate dorsal–ventral patterning and anterior–posterior placement of the embryo in the hemipteran Rhodnius prolixus

Abstract: BackgroundInsect embryonic dorso-ventral patterning depends greatly on two pathways: the Toll pathway and the Bone Morphogenetic Protein pathway. While the relative contribution of each pathway has been investigated in holometabolous insects, their role has not been explored in insects with a hemimetabolous type of development. The hemimetabolous insect Rhodnius prolixus, an important vector of Chagas disease in the Americas, develops from an intermediate germ band and displays complex movements during katatre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 63 publications
(87 reference statements)
5
66
0
3
Order By: Relevance
“…We identified single-copy orthologs for the DV patterning genes, including most Toll and bone morphogenetic protein (BMP) pathway elements. The BMP type I receptor Sax, however, was not found in R. prolixus or in previous analyses (30). Our functional analysis showed that one of the rpToll genes (RPRC009262), similarly to that reported for hymenopterans (31,32), performs both DV and AP embryonic patterning roles (30), pointing to a potentially novel role that this pathway element might display during embryogenesis.…”
Section: Significancementioning
confidence: 57%
“…We identified single-copy orthologs for the DV patterning genes, including most Toll and bone morphogenetic protein (BMP) pathway elements. The BMP type I receptor Sax, however, was not found in R. prolixus or in previous analyses (30). Our functional analysis showed that one of the rpToll genes (RPRC009262), similarly to that reported for hymenopterans (31,32), performs both DV and AP embryonic patterning roles (30), pointing to a potentially novel role that this pathway element might display during embryogenesis.…”
Section: Significancementioning
confidence: 57%
“…During early stages the polarity of the embryo and of the egg are coincident, but during the movements of anatrepsis they become everted regarding AP and DV axes. At later stages (stage 9 and 10 from Berni et al, ), katatrepsis reestablishes the coincidence of egg and embryonic polarity. Head and gnathal segments are displayed in blue, thoracic in yellow and abdominal in green.…”
Section: Embryonic Developmentmentioning
confidence: 92%
“…Knock‐down of Rp‐Dorsal , a transcription factor of the Toll pathway also did not change T. cruzi parasite levels (Mesquita et al ., ). The fact that the expression of the Iĸ‐B inhibitor Rp‐cactus is up‐regulated after Zymosan exposure (Berni et al ., ) indicates that the Dorsal pathway is indeed involved in immunity in hemiptera, although not stimulated by T. cruzi infection. Thus, T. cruzi probably developed active evasion or tolerance mechanisms, which is absent in the Rhodococcus symbiotic bacteria.…”
Section: Hemiptera Species For Developmental Studies and Their Relatimentioning
confidence: 96%
See 2 more Smart Citations